Results of Coarctation Repair by Thoracotomy in Pediatric Patients: A Single Institution Experience. Issue 4 (July 2021) - Heremans, Louis; Henkens, Arnaud; de Beco, Geoffroy; Carbonez, Karlien; Moniotte, Stéphane; Rubay, Jean E.; Momeni, Mona; Houtekie, Laurent; Poncelet, Alain J.
Background: Aortic coarctation is among the most common cardiovascular congenital abnormalities requiring repair after birth. Besides mortality, morbidity remains an important aspect. Accordingly, we reviewed our 20-year experience of aortic coarctation repair by thoracotomy, with emphasis on both short- and long-term outcomes. Methods: From 1995 through 2014, 214 patients underwent coarctation repair via left thoracotomy. Associated arch lesions were distal arch hypoplasia (n = 117) or type A interrupted aortic arch (n = 6). Eighty-four patients had isolated coarctation (group 1), 66 associated ventricular septal defect (group 2), and 64 associated complex cardiac lesions (group 3). Median follow-up was 8.4 years. Results: There was one (0.5%) procedure-related death. Nine (4.2%) patients died during index admission. In-hospital mortality was 0.7% in group 1 and 2 and 12.5% in group 3 ( P < .001). No patient had paraplegia. Actuarial five-year survival was 97.5% in group 1, 94% group 2 and 66% in group 3. Recurrent coarctation developed in 29 patients, all but four (1.8%) successfully treated by balloon dilatation. Freedom from reintervention (dilatation or surgery) at five years was 86%. At hospital discharge, 28 (13.5%) patients were hypertensive. At follow-up, hypertension was present in 11 (5.3%) patients. Conclusions: Long-term results of aortic coarctation repair by thoracotomy are excellent, with percutaneous angioplasty being the procedure of choice for recurrences. Patient prognosis is dependent on associated cardiac malformations. In this study, the prevalence of late arterial hypertension was lower than previously reported.